KARAKTERISTIK MINERALOGI ENDAPAN NIKEL LATERIT DI DAERAH TAMBANG TENGAH (BUKIT TLA2) PT. ANTAM Tbk. UBP NIKEL POMALAA SULTRA - -, Musnajam (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
This research is aimed to understand the mineralogy of nickel laterite deposit and geochemistry of ultramafic rock, the samples were taken from 14 drilling holes The data is analyzed to conduct weathering geochemical profile to identify lateritization, laterite profile development, characteristics and elements enrichment process in weathering zones. Lithology of the study area is composed by dunite and lherzolite, That dominated by livine, pyroxene and serpentine, also opaque minerals such as chromite and magneti-te with small percentage. Based on X-Ray Diffraction analysis known that the clay mine-rals are chlorite, clinochlore, kaolinite, and dyckite. Based on geochemical analyzes, the mineralogy characteristics of study area showing the different behavior for each element, due to the weathering rate and the dept of cores. The different behavior each element during weathering process determined by different element chemical mobility, forming minerals resistance, weathering intensity and jointing process.